Incorpórese en la Ley De Gestión Ambiental, garantías a la biodiversidad del medio ambiente en relación al desarrollo económico del Ecuador - Vásquez Jaramillo, Tuesman Iván (2015)
Environmental impact, as human activity is the product of contamination, negligent actions, as the oil spill in the pipeline damage, or work activities, such as using chemicals to extract minerals and affecting water, soil and subsoil where they perform mineral holdings. To this the state through appropriate policies intervene to minimize the environmental impact by human activity, as a means of producing wealth, activities that should prevent foreseeable consequences through a discussion between business and the entrepreneurial role. The environment is no stranger to the human race, physical, chemical and biological characteristics of the environment around us offer the optimal framework for our development, the environment is defined as all the elements that surround us, living or inert, plus their interrelationships and are a substantial part of half mega-diverse environment that are part of the development of natural systems, but environmental pollution has an effect of loss of function that has been developing ecosystems, loss of living components, its micro organisms, species, has a special significance in the social environment, and directly with living things, and that the Constitution guarantees the development of life to the principle of Good Living; but the environmental objective reality is different, as there is a shock, a real and undeniable conflict between economic interests concerning the production of goods for the life of human beings and the desirability of maintaining nature, not damage it, not destroy it, in short, protecting the environment, therefore the own economic expansion of civilized progress, appears hopelessly tied a demand for personal interests, leading to the depletion of natural resources,! biological and multiplicity of life, therefore Biodiversity, in conclusion follows that the constitutional precepts lead to the need for legislation competently, for the protection of both legal rights, and primacy for the environment living space and economic development